Clytemnestra and her shadow. The female character in the plays or Aeschylus - Guillén, Luis F. (Tropelías: Review of Literary Theory and Comparative Literature, 1993)
"Clytemnestra and her shadow" has a threefold purpose. Firstly, it sets out to explore the Aristotelian concept of ’character’ and attempts to mark out its theoretical limits and its validily for an analysis of the characters of Greek tragedy. Secondly, it attempts to show that Aeschylus is able not only to create ’characters’ but also to endow certain characters with a quintessential feature of femininity. Clytemnestra is taken for purposes of analysis in her twofold condition of ’character’ and woman. The text that best brings out this twofold condition is the dialogue with her husband (Ag. 810-974) in the magnificent reception scene in the first parl of the Orestia. Finally, a comparison with Lady Macbeth reveals the universal value of their female character. Their feminine profile is enhanced when they are seen in terms of their parallel roles: as conspirators in a crime, as spouse-cum-murderers, as influenced by the masculinizing effect of tension, as subject to the male-female dialectic, the possibility of erotic motivation, etc.